Optimal control for a class of compartmental models in cancer chemotherapy - Świerniak, Andrzej (1950- ); Ledzewicz, Urszula; Schättler, Heinz (Zielona Góra: Uniwersytet Zielonogórski)
We consider a general class of mathematical models P for cancer chemotherapy described as optimal control problems over a fixed horizon with dynamics given by a bilinear system and an objective which is linear in the control. Several two- and three-compartment models considered earlier fall into this class.
Keywords: compartmental models; cancer chemotherapy; optimal control; necessary and sufficient conditions for optimality